2015
DOI: 10.3892/mmr.2015.3826
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-148a inhibits the proliferation and promotes the paclitaxel-induced apoptosis of ovarian cancer cells by targeting PDIA3

Abstract: MicroRNAs (miRs) are a class of non-coding RNAs that function as key regulators of gene expression at the post-transcriptional level. miR-148a has been suggested to be associated with human ovarian cancer, however, the detailed functions of miR‑148a in ovarian cancer remain to be fully elucidated. The present study aimed to investigate the regulatory mechanism of miR-148a in ovarian cancer cells. Reverse transcription‑quantitative polymerase chain reaction and western blot analysis were conducted to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
3
9
0
10
Order By: Relevance
“…In multiple types of tumors, such as ovarian cancer, miR148a acts as a tumor suppressor to inhibit the growth of cancer cells [12,28,29]. However, a number of studies argue that miR-148a acts as an oncomiR or tumor suppressor depending on the tumor types.…”
Section: Discussionmentioning
confidence: 97%
“…In multiple types of tumors, such as ovarian cancer, miR148a acts as a tumor suppressor to inhibit the growth of cancer cells [12,28,29]. However, a number of studies argue that miR-148a acts as an oncomiR or tumor suppressor depending on the tumor types.…”
Section: Discussionmentioning
confidence: 97%
“…A number of previous studies have shown associations of the proteins selected in this study, especially the four upregulated proteins (MIF, THBS1, PDIA3, and APOA1), with various features of cancer pathophysiology in liver cancer, as well as other types of cancers (Supplementary Table S7 ): (1) MIF was reported to be increased at both the mRNA and protein levels in liver cancer tissues compared to noncancerous tissues 65 and to promote tumor survival, angiogenesis, and/or metastasis in colon, head and neck, liver, and/or prostate cancers; 65 68 (2) THBS1 was shown to be elevated in liver cancer 69 and to promote tumor survival, aggressiveness, angiogenesis, and metastasis in breast, bladder, liver, gastric, prostate, and/or pancreatic cancers; 69 74 (3) PDIA3 was reported to be elevated in liver cancer 75 and to enhance the proliferation of tumor cells, metastasis, and/or invasion in breast, colon, ovarian, and/or pancreatic cancers; 75 79 and (4) APOA1 was observed to be elevated in the serum of liver cancer patients 80 , as well as in the serum of breast, colon, and lung cancers 81 83 and in the urine of bladder cancer 84 , and its abundance showed positive correlations with aggressiveness and/or metastasis in bladder, colon, and lung cancers 82 , 85 , 86 . These data suggest that the secreted proteins with various tumors might serve as a secretome profile that can represent cancer pathophysiology, such as the proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ectopic expression of miR-148a sensitized the cells to TRAIL via the down-modulation of matrix metalloproteinase 15 (MMP15) and Rho-associated kinase 1 (ROCK1) in non-small cell lung cancer (22). In addition, enforced expression of miR-148a promotes paclitaxel-induced apoptosis of ovarian cancer cells by targeting PDIA3 (23). miR-148a was found to induce apoptosis and activate the caspase-dependent pathway, indicating that it might function as a tumor suppressor in renal cancer cells.…”
Section: Discussionmentioning
confidence: 99%